ANALYSIS OF EMPLOYEE PERFORMANCE DETERMINATION FACTORS - Jasin, Hanifah; Fitri, Rizkia Roza (International Proceeding of Law and Economic, 2021)
The purpose of this study was to determine and analyze the effect of compensation on employee performance, to determine and analyze the effect of career development on employee performance and to determine and analyze the effect of compensation and career development on employee performance at PT. Beautiful Clothing. The approach used in this study is an associative approach. The population in this study were all employees of PT. Indah Busana, totaling 60 employees. while the sample that meets the criteria for sampling the observations made is 60 employees using a saturated sample. Data collection techniques in this study used questionnaires and interviews. The data analysis technique in this study uses Multiple Linear Regression Test, Classical Assumption Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) software program version 24.00.